Pengaruh Sistem Remunerasi dan Penilaian Kerja Terhadap Kinerja Karyawan PT Istana Prima Esa - Yuli Anwar (STIE Binaniaga, 2009)
Implementation of a clear system of remuneration and to be fair to all employees at all levels of office can provide motivation to employee performance so it will be the human form of competent and qualitified companies. In other word the expected relationship management system of remuneration which is applied against the employee can improve employee performance in work environment so that it can increase company productivity. The analysis showed that (1) of the Remuneration System Employee Performance there was a positive relationship and significant at a value r + 0.478 and a significance of probilitas 0000 <= 0.05, then there is a positive and significant between Remuneration of Employees Performance shown with a regression coefficient value of 0.272 and 0.000 significance probability <0.05, whereas the contribution system which explains the performance of Employee Remuneration of 22.9%, while the regression equation is Y + 19.573 + 0.272X1, (2) of Assessment Work with Employee Performance there and positive relationship was significant with a value of r + 0.543 and a significance of probilitas 0000 <= 0.05, then there is a significant and positive effect between Employee Performance Assessment Working against the value shown by the regression coefficient of 0.302 and 0.000 significance probability of <0.05, while the contribution of Assessment Work which explains 29.4% of Employee Performance, while the contribution of Assessment Work which explains of Employee Performance, while the regression equation is Y = 20.500 + 0.302 X2 and simultaneously the relationship between Remuneration and Employee Performance Assessment Work with positive and significant areindicated by the value of the correlation coefficient of 0.557. In addition there are jointly significant and positive influence Remuneration and Employee Performance Assessment Working against, while the contribution of Remuneration and Appraisal Employee Performance Work which explains 33.3%. The regression equation to expresss the influence of Remuneration System (X1) and Assessment of Work (X2) of the Employee Performance (Y) is Y = 18.269+0.139+0.223X1 X2.